Standard forms of contract and its influence on construction professionals - Othman, Norazam (Faculty of Built Environment, UTM, 2008)
The aim of the research is to investigate influence of standard forms of contract or conditions of contract on construction professionals. Standard forms are constantly being amended, modified and even totally revamped on the basis that these are one of the primary sources of conflicts and disputes in the construction industry. Unwittingly the drafting of newer forms to mitigate future disagreement also presents evidence that the stakeholders adhere and subscribe to the philosophy and theoretical idealisations of contract law, which promises compliance, thus resulting in predetermined and predictable act or action. The behaviour of construction professionals are shaped thus influenced by this classical model of contract, as codified. However previous research has shown that this premise flawed and requires investigation and further study. Research questions were directed to elucidate how and why contractual rules and procedures are used whenever construction professionals are doing their task. Data to be collected is the thoughts and actions of the professionals who used procedures in dealing with a specific task. Content analysis of the semi- structured interviews were conducted to discover the meanings that a respondent actually alluded to since it is located and indexed within the expressions used to describe, explain or justify a specific task, event or occasion. The interviews were recorded, transcribed to written form and text. Due to the massive amount of data, the coding framework was approached by utilising a computer software that permits manipulation and proper categorisation and retrieval. Finally, framing the research within a case study methodology ensures the preservation of the unitary character of the social object being studied. Findings indicate that although construcion professionals are influenced by procedures and/or rules codified in standard forms of contract, other traces also present. The findings could be used to identify more robust drafting policies of newer standard forms or conditions of contract rather than insuanating that present documents are less than ideal due to its clarity or other factors that suggest that the contract is the main source of conflicts and disputes. The mode of inquiy adopted means that the research is not concerned with noting frequency or occurences of usage contractual procedures and/or rules but rather illustrate and identify these influences.